PROSES ARTISTIK DALAM PRODUKSI FILM DOKUMENTER "MUSEUM INSTAGRAMMABLE" - Santyaputri, Lala Palupi; David, Samuel (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Technological development led to the use of devices equipped with better quality cameras constructs museum visitors who come to document and shared the experience of museum walking. Through this documentary, the author investigates how one social network, specifically Instagram, can change people's motives for visit museums. Qualitative methods, based on interviews with museum visitors in Indonesia and also interviews with education experts, as well as art consultants, the authors reveal the phenomena that occur in the museum world, especially in Indonesia. Through this documentary, it is hoped that the use of devices and social networks is not the only reason to visit the museum but help to increase the appreciation of the Indonesian for art and museums. Keywords: museum, pictures, instagramable